Social networks and quality of life of elderly persons: a review and critical analysis of literature - Odília Maria Rocha Gouveia; Alice Delerue Matos; Maria Johanna Schouten (Revista Brasileira de Geriatria e Gerontologia, 2016)
Abstract Several studies have documented the importance of social networks for quality of life (QL) in old age. This article presents a review and critical analysis of the literature on the relationship between the social networks of the elderly and their QL/well-being. A survey using interdisciplinary search engines [Web of Knowledge, Scopus, Scholar Google, Science Direct and Online Knowledge Library (b-on)], followed by an in-depth examination of the 37 documents subsequently identified, selected based on content, the geographical context of the study and its publication date, suggested a number of tendencies. In the first place, networks of friends have a greater impact on the QL/well-being of elderly persons than family networks. Secondly, the positive effect of the existence of more than one type of relationship was revealed (such as simultaneous friendships and family relationships). Finally, literature suggests emotional closeness has a positive impact on QL/well-being. The present study exposed the lack of longitudinal studies into the causality between network characteristics and QL/well-being. It also revealed the lack of research on the relationship between social networks and QL/well-being in elderly persons living alone. One problematic aspect relates to the fact that few studies provide a definition of the QL measures they adopt, or the rationale behind the manner of their operationalization of the concept.